THINKING ORDER SKILLS OF READING COMPREHENSION QUESTIONS IN ENGLISH TEXTBOOK FOR ELEVENTH GRADE OF SENIOR HIGH SCHOOL BASED OF BLOOM’S TAXONOMY - Nurasiah Lubis; Busmin Gurning; Masitowarni Siregar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
The objective of this study aimed to analyzing higher order thinking skills of reading comprehension questions in English textbook for eleventh grade of senior high school. It also used qualitative research method for collected, analyzed and classified reading questions based on revised of Bloom’s Taxonomy. The data of this study were taken from reading comprehension questions in Contextual English textbook. The findings showed that the distribution of the higher order thinking skills looks like: the analyze skill obtains 20 out of 155 reading comprehension questions (12.9%) while the evaluate skill only obtains 4 out 155 questions (2.6%) and the create skill obtains 2 out of 155 questions (1.2%). The dominant level of the higher order thinking skills contained in analyze skill (12.9%). These results do not achieve proportion of thinking order skills namely 30% for C1 and C2, 40% for C3 and C4, and 30% for C5 and C6. It shows that the distribution of the higher order thinking skills in the reading comprehension questions in Contextual English textbook is unequal. Key words: English language textbook, reading comprehension questions,revised edition of Bloom’s Taxonomy.